Peranan Tokoh Intelektual Muda dalam Perkembangan Politik di Indonesia pada Era Digital - Annisa Vira; Pulung Sumantri; Abdul Azis (Medan Resource Center, 2024)
Democracy's vitality in a nation hinges on the depth of political engagement, evident when the populace actively participates in events like presidential and regional elections. The level of political involvement serves as a pivotal gauge for a country's democratic progress, reflecting genuine concern for political development. This engagement, influenced by diverse societal groups, notably the youth, holds significance. Generation Z and Millennials, the key demographics, wield considerable influence, with Generation Z earning the moniker